Photoelectrochemical N2-to-NH3 Fixation with High Efficiency and Rates via Optimized Si-Based System at Positive Potential versus Li0/+ - Zhang, X.; Lyu, Y.; Zhou, H.; Zheng, J.; Huang, A.; Ding, J.; Xie, C.; De Marco, Roland; Tsud, N.; Kalinovych, V.; Jiang, San Ping; Dai, L.; et al. (2023)
As a widely used commodity chemical, ammonia is critical for producing nitrogen-containing fertilizers and serving as the promising zero-carbon energy carrier. Photoelectrochemical nitrogen reduction reaction (PEC NRR) can provide a solar-powered green and sustainable route for synthesis of ammonia (NH3). Herein, an optimum PEC system is reported with an Si-based hierarchically-structured PdCu/TiO2/Si photocathode and well-thought-out trifluoroethanol as the proton source for lithium-mediated PEC NRR, achieving a record high NH3 yield of 43.09 µg cm−2 h−1 and an excellent faradaic efficiency of 46.15% under 0.12 MPa O2 and 3.88 MPa N2 at 0.07 V versus lithium(0/+) redox couple (vs Li0/+). PEC measurements coupled with operando characterization reveal that the PdCu/TiO2/Si photocathode under N2 pressures facilitate the reduction of N2 to form lithium nitride (Li3N), which reacts with active protons to produce NH3 while releasing the Li+ to reinitiate the cycle of the PEC NRR. The Li-mediated PEC NRR process is further enhanced by introducing small amount of O2 or CO2 under pressure by accelerating the decomposition of Li3N. For the first time, this work provides mechanistic understanding of the lithium-mediated PEC NRR process and opens new avenues for efficient solar-powered green conversion of N2-to-NH3.